PENGARUH MEDIA CANVA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 091281 BATU IV - Kisah Dora Julianty Samosir; Theresia Monika Siahaan; Jon Roi Tua Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low mathematics learning outcomes of fourth-grade students at SD Negeri 091281 Batu IV, who have not yet achieved the KKTP (Qualification Level) of 70, due to conventional learning and a lack of innovative media. This study aimed to determine the effect of using Canva on mathematics learning outcomes for fractions in the 2025/2026 academic year. Using a quantitative approach with a one-group pretest-posttest design, the study sample included all 26 fourth-grade students. Data were collected through multiple-choice tests and analyzed using t-tests and N-Gain. The results showed an increase in the average score from 52 (pretest) to 90.30 (posttest). The N-Gain test of 0.75 indicated a high level of effectiveness. The results of the paired-sample t-test obtained a significance value of 0.00 < 0.05, indicating a significant difference between learning outcomes before and after the treatment. It was concluded that the use of Canva significantly improved the mathematics learning outcomes of fourth-grade students at SD Negeri 091281 Batu IV. Keywords: Canva Media, Mathematics Learning Outcomes, Fractions, Elementary School.